A study of the preparation of "toyo" from bush sitao (Vigna sinensis var. sesquipedalis) - Sustento, Lydia Anino 1922-
This study focuses on the feasibility of using cheaper local beans as raw material in the manufacture of soy sauce. Bush sitao and corn flour were used as raw materials for the sauces prepared through the fermentation method. Two proportions of the bean to the corn flour were tried and varying concentrations of salt solution were tested.